The fledgling - Langton, Jane.; Blegvad, Erik. (New York : Scholastic Inc., 1981)
Georgie's fondest hope, to be able to fly, is fleetingly fulfilled when she is befriended by a Canada goose.
"An Ursula Nordstrom book."
Accelerated Reader AR
Keywords: Fantasy; Canada goose -- Fiction; Flight -- Fiction